2017
DOI: 10.1111/cdev.12893
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Learning and Spelling: Older Prephonological Spellers Produce More Wordlike Spellings Than Younger Prephonological Spellers

Abstract: The authors analyzed the spellings of 179 U.S. children (age = 3 years, 2 months-5 years, 6 months) who were prephonological spellers, in that they wrote using letters that did not reflect the phonemes in the target items. Supporting the idea that children use their statistical learning skills to learn about the outer form of writing before they begin to spell phonologically, older prephonological spellers showed more knowledge about English letter patterns than did younger prephonological spellers. The writte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…Although there were a few differences, the many similarities between the present results with Brazilian prephonological spellers and the previous findings with US prephonological spellers (Treiman et al, 2018) are striking because of the differences in orthographic depth between Portuguese and English. Many studies have shown that the orthographic depth of a writing system strongly influences spelling and reading development (e.g., Serrano et al, 2011; Seymour et al, 2003).…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Although there were a few differences, the many similarities between the present results with Brazilian prephonological spellers and the previous findings with US prephonological spellers (Treiman et al, 2018) are striking because of the differences in orthographic depth between Portuguese and English. Many studies have shown that the orthographic depth of a writing system strongly influences spelling and reading development (e.g., Serrano et al, 2011; Seymour et al, 2003).…”
Section: Discussionsupporting
confidence: 59%
“…To assess the degree to which children used letters in proportion to their frequency in the language and whether this varied as a function of age, we computed for each child a version of the monogram correlation measure used in previous studies (Kessler et al, 2013; Treiman et al, 2018). To compute this measure, we summed the frequency with which a child used each letter of the alphabet across all of the spellings in each test and calculated the Kendall rank correlation coefficient (xb) between these values and the frequency counts of the letters in texts for preschool children, based on the word counts of Pinheiro (1996).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations